KOSAKATA VERBA DALAM LIRIK-LIRIK LAGU MELAYU SANGGAU KARYA M. RIVA’I NAPIS - Ningrum, Tri Desi Anggraini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aims to observed the vocabulary verbs in the lyrics of Sanggau Malay Song by M. Riva’i Napis. It has three main problems, those are (1) describing of verbs component meaning in the lyrics of Sanggau Malay Song by M. Riva'i Napis, (2) describing kind of meaning and definition of verbs vocabulary meaning in the lyrics of Sanggau Malay Song by M. Riva'i Napis, and (3) describing of semantics function of verbs vocabulary in the lyrics of Sanggau Malay Song by M. Riva'i Napis. Research method used in this research is descriptive qualitative. The result of this research is, there are 166 lexemes of verbal glossaries, either it is an active or passive verbal, there are 75 lexemes in 27 component classification meaning, 166 lexemes lexical meaning, 104 lexemes grammatical meaning caused by affixation, reduplication, and complexities, 6 figure of speech, and 131 lexemes which used as predicate with subject function 104 total of lexemes, target function 63 lexemes total, pengalam function 23 lexemes total, peruntung function 19 lexemes total, information function (place) 30 lexemes total, information function (time) 6 lexemes total, and information function (tool) 1 lexeme total. Keywords: the vocabulary verbs, Sanggau Malay Song’s lyrics, component meaning, kind of meaning and definition, semantics function